Pengaruh Komunikasi, Kecerdasan Emosional, dan Iklim Kerja Terhadap Kinerja Karyawan di Prasi Hospitality di Kabupaten Gianyar - I Wayan Budi Ugi Adnyana; Ni Ketut Sukanti; Ni Putu Yuliana Ria Sawitri (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
The success of a company depends on the work achievements of employees. Communication between fellow employees and superiors, employees' emotional intelligence, and work climate determine the performance produced by employees. The purpose of this study is to determine the influence of communication, emotional intelligence, and work climate partially and simultaneously on the performance of Prasi Hospitality employees. A total of 70 employees became the population in this study and by using saturated sampling, a sample of 70 respondents was obtained. The data analysis used in this study is the classical assumption test, multiple linear regression analysis, determination analysis, partial significance test (t-test), and simultaneous significance test (F-test). The results of the study prove that communication, emotional intelligence, and work climate partially and simultaneously have a positive and significant effect on employee performance at Prasi Hospitality. Communication between fellow employees that is well established, supported by high emotional intelligence and a good work climate, tends to encourage employees to achieve optimal performance.